Therapeutic Potential of Ascorbic Acid in the Management of Alzheimer's Disease: An Update - Semwal, Bhupesh C.; Singh, Bhoopendra; Murti, Yogesh; Singh, Sonia (Current Pharmaceutical Biotechnology, 2024)
Background: Ascorbic acid is a potent natural antioxidant that protects against oxidative stress and performs various bodily functions. It is commonly found in fruits and vegetables. Objective: The manuscript has been written to provide valuable insights into ascorbic acid in managing Alzheimer's disease. Methods: The data has been gathered from web sources, including PubMed, Science Direct, Publons, Web of Science, and Scopus from 2000-2022 using AA, ascorbic acid, Alzheimer’s diseases, memory, dementia, and antioxidant keywords. Results: In the present manuscript, we have summarized the impact of ascorbic acid and its possible mechanism in Alzheimer's disease by, outlining the information currently available on the behavioral and biochemical effects of ascorbic acid in animal models of Alzheimer's disease as well as its usage as a therapeutic agent to slow down the progression of Alzheimer disease in human beings. Oxidative stress plays a significant role in the advancement of AD. AA is a wellknown antioxidant that primarily reduces oxidative stress and produces protein aggregates, which may help decrease cognitive deficits in Alzheimer's disease. The current paper analyses of ascorbic acid revealed that deficiency of ascorbic acid adversely affects the central nervous system and leads to cognitive defects. However, the results of clinical studies are conflicting, but some of the studies suggested that supplementation of ascorbic acid improved cognitive deficits and decreased disease progression. Conclusion: Based on clinical and preclinical studies, it is observed that ascorbic acid supplementation improves cognitive deficits and protects the neurons from oxidative stress injury.
Keywords: MAPK